Apuntes históricos sobre el pronombre indefinido omne - Zieliński, Andrzej (Neophilologica, 2012)
The aim of the paper is to analyze the origin and the grammaticalization of the indefinite pronoun omne in Old and Middle Spanish. Basing on the relatively large corpus of literary texts, we will find the reasons of its fading since the XVI century.